2013
DOI: 10.1080/09585192.2013.809013
|View full text |Cite
|
Sign up to set email alerts
|

Hablas vielleicht un peu la mia language?A comprehensive overview of the role of language differences in headquarters–subsidiary communication

Abstract: The management of human resources in headquarters (HQ)-subsidiary relationships requires intensive communication, but effective communication often depends on having a shared language. Hence, language differences can be a serious threat to the successful management of human resources in multinational corporations (MNCs). In this large-scale quantitative study, encompassing data from more than 800 subsidiaries in thirteen countries, we investigated four related issues. First, in terms of the importance of langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…Harzing and her colleagues (Feely and Harzing 2002;Harzing et al 2011;Harzing and Pudelko 2013) carried out a series of mainly quantitative studies that look into the 'language barrier' in multinational companies, which refers to language differences that lead to communication problems. Feely and Harzing (2002) distinguish three dimensions of the language barrier: (1) language diversity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Harzing and her colleagues (Feely and Harzing 2002;Harzing et al 2011;Harzing and Pudelko 2013) carried out a series of mainly quantitative studies that look into the 'language barrier' in multinational companies, which refers to language differences that lead to communication problems. Feely and Harzing (2002) distinguish three dimensions of the language barrier: (1) language diversity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Firm-level research focuses on language competencies, policies, and practices within MNCs (e.g., Harzing and Pudelko 2013), including HQ-subsidiary relationships (Harzing et al 2011;Harzing and Pudelko 2014) and mergers, acquisitions, and alliances (Joshi and Lahiri 2014;Cuypers et al 2015). These studies investigate the impact of linguistic diversity on social identity formation (e.g.…”
Section: Firm Level Perspectivesmentioning
confidence: 99%
“…Language has moved from being treated as an operative and peripheral issue to becoming a strategic concern for a growing number of IB researchers (Luo and Shenkar, 2006). Recent research has shown how language diversity in multinational corporations (MNC) affects core management processes such as effectiveness of communication (Harzing and Pudelko, 2014), knowledge transfer between subsidiary units (Peltokorpi and Vaara, 2014;Reiche et al, 2015) and overall sense of belongingness and cohesion among geographically dispersed employees (Neeley, 2017). IB research often takes a structuralist, design-based view of the organisation and illustrates well the complex co-existence of multiple languages at work.…”
Section: Introductionmentioning
confidence: 99%